Public open space’s contribution to quality of life : does privatisation matters? / Achmad Delianur Nasution and Wahyuni Zahrah - Zahrah, Wahyuni (Faculty of Architecture, Planning and Surveying, 2012)
Quality of life of people in urban area is the outcome of people interaction with urban environment. Many studies indicate that public open space is one of important urban environment elements which give positive contribution to quality of life. This paper investigates how privatization of public open space affects quality of life of people while many studies show degradation of 'publicness' of public space due to privatization. Research finding indicates that people keep doing their social activities both in privatized and public area but physically segregated.